Osgood-Schlatter Disease in an Adult Athlete: A Case Report and Review of the Literature - Arash Sharafat Vaziri; Nazanin Rahimdoost; Soodabeh Esfandiary; Fardis Vosoughi; Mehdi Moezi; Iman Menbari Oskouie (Journal of Orthopedic and Spine Trauma)
Osgood-Schlatter disease (OSD), a form of traction apophysitis, predominantly affects adolescents engaged in high-impact activities. While conservative management is often effective, surgical intervention becomes necessary in refractory cases. This case report details an innovative arthroscopic approach to treat adult OSD, where traditional methods failed. A 29-year-old male athlete with persistent OSD symptoms underwent arthroscopic surgery after unsuccessful non-surgical treatments. The procedure, utilizing a unique combination of portals, demonstrated positive clinical and radiological outcomes. Arthroscopic removal of the bony particle was undertaken using six portals with a novel setting (consisting of medial and lateral superior, standard, and inferior portals) to minimize the damage to the patellar tendon and intermeniscal ligaments. This setting of portals also obviates the need for fluoroscopy since it provides adequate visualization for confirmation of complete removal of the bony particle. The lower portals also provide more convenient access to the bony particle, minimizing the possibility of incomplete removal and persistence of symptoms. The patient experienced complete resolution of anterior knee pain and prominence within six months post-surgery. Arthroscopic removal of the ossicle involved the use of superior portals for optimal access and visualization. Low portals were strategically employed to eliminate the need for fluoroscopy, offering a unique advantage. Postoperative rehabilitation included immobilization followed by a gradual return to weight-bearing and full range of motion. Arthroscopic removal remains the preferred method for treating OSD, emphasizing fewer complications. However, challenges related to limited access and anatomical restoration persist.